Overcoming Shyness and Bullying in EFL Classrooms: Strategies for Promoting Communicative Competence among Iraqi Learners (Journal of Misan Researches, 2024)
The improvement of communicative competence in English as a Foreign Language (EFL) is essential for Iraqi learners to involve effectively in personal, academic, and professional contexts. However, learners often face obstacles like shyness and bullying that could hinder their language acquisition and participation in classroom activities. This research examines strategies to overcome those obstacles and endorse a supportive learning environment that nurtures communicative capability amongst Iraqi EFL learners. Through a wide-ranging literature review, the study inspects theoretical perspectives from the affective filter hypothesis, sociocultural theory, and motivational backgrounds to comprehend the multidimensional factors influencing language learning practices.  The conceptual model offered integrates individual factors (shyness, anxiety, motivation), social features (bullying, peer relationships, classroom climate), and pedagogical methods to explore their relationship in developing communicative competence. The research theorizes that targeted interventions, like affective strategies, anti-bullying programs, and supportive learning techniques, can alleviate the negative impacts of shyness and bullying, thereby enhancing learners' communicative capabilities. The findings have important implications for EFL teaching practices in Iraq, highlighting the importance of creating inclusive classrooms, applying communicative language teaching approaches, cultivating peer support, and addressing socio-cultural effects. Eventually, this study contributes to the body of knowledge on endorsing communicative competence and presents applied references for educators, policymakers, and shareholders in the arena of EFL education in Iraq.